Microspatial Heterogeneities and the Absence of Postmortem Contamination in Alzheimer’s Disease Brain Microbiota: An Alzheimer’s Pathobiome Initiative (AlzPI) Study - Myat N. Thwe; Yves Moné; Bhaswati Sen; Samuel Czerski; Ahmed Azad; Joshua P. Earl; Donald C. Hall; Garth D. Ehrlich (Microorganisms)
The discovery of profound differences in the brain microbiota of Alzheimer’s disease (AD) patients and age-matched controls (AMCs) raised questions of postmortem contamination and bacterial transport processes which could be informed by microspatial heterogeneities. We performed semiquantitative species-specific bacterial analyses on multiple micro biopsies from each of the 30 brain specimens (AD and controls). We trimmed ~1 mm of each specimen’s edges for surface contaminants and made multiple sterile biopsy punches of the resultant core of each specimen. To identify species-specific abundances, we used our validated, semiquantitative, full-length 16S rRNA gene pan-domain amplification protocol followed by high-fidelity circular consensus sequencing performed on a Pacific Biosciences Sequel IIe instrument. Statistical analyses showed no significant increase in bacterial abundance on trimmed surfaces compared to core specimens, including C. acnes, the most abundant species previously identified in AD. We did find evidence of substantial bacterial species abundance differences among micro-biopsies obtained from within individual tissue blocks supporting our hypothesis of microspatial heterogeneities. The autopsy brain specimens used in our analyses in this study and our previous publication were not contaminated prior to or postharvesting but we suggest that future microbiological analyses of brain specimens include similar types of edge-core comparison analyses. Further, the species-level bacterial abundance heterogeneities among specimens of the same tissue suggest that multiple symbiotic processes may be occurring.